Patients with tinnitus use more primary healthcare compared to people without tinnitus - Maaike Maartje Rademaker (Nature Portfolio, 2021)
Abstract Tinnitus is a heterogeneous condition not only in terms of nature of the sound, but also in co-morbidities such as mental health issues. Prevalence number range widely between 5 and 43%. Even though the etiologic pathway between tinnitus and its comorbidities remains unclear, in this study we aim to assess whether people with tinnitus use more primary health care than people without tinnitus. To compare primary healthcare consumption between patients with tinnitus and people without tinnitus. In this cross-sectional study, data on number of consultations with the general practitioner or nurse practitioner mental health services were obtained from Nivel (Netherlands Institute for Health Service Research) Primary Care Database in 2018 (n = 963,880 people). People with an open tinnitus episode (n = 8050) were defined as a patient with tinnitus and compared to all other people. Percentages, means, ranges and mean differences were calculated for the total number of consultations and for organ specific diagnoses registered as ICPC-1 code on the day of consultation. Secondary, the total number of referrals to medical specialists and number of drug prescriptions was collected. Logistic regressions were performed to predict having one or more contacts, referrals, and prescriptions,with having tinnitus, this was corrected for age and gender. Patients with tinnitus had a mean of 9.8 (SD 10.9) primary care consultations in 2018, compared to 5.7 (SD 7.9) for people without tinnitus. More patients with tinnitus had more than one referral to medical specialists (47%) compared to people without tinnitus (25%). Patients with tinnitus have 1.2 (mean difference) more drug prescriptions than people without tinnitus. Compared to people without tinnitus, patients with tinnitus were more likely to have one or more of primary healthcare contact, independent of age group and gender. Patients with tinnitus had more consultations in primary health care than people without tinnitus. They are more often referred to medical specialists and receive more drug prescriptions. The causal relationship between tinnitus and the higher healthcare consumption remains to be researched.